Towards sustainable road transport - Dell, Ronald (Academic Press, 2014)
Increasing pressure on global reserves of petroleum at a time of growing demand for personal transport indeveloping countries, together with concerns over atmospheric pollution and carbon dioxide emissions, areleading to a requirement for more sustainable forms of road transport. Major improvements in the efficiencyof all types of road vehicles are called for, along with the use of fuels derived from alternative sources, orentirely new fuels. Towards Sustainable Road Transport first describes the evolution of vehicle designs andpropulsion technologies over the.